POLA KECERDASAN EMOSI PESERTA DIKLAT LPJ POLA KHUSUS K1 DAN K2 PADA DINAS PENDIDIKAN KOTA PEKANBARU - Sugiarto, Sugiarto (Jurnal Pendidikan Guru, 2017)
Participants of LPJ CPNS Special Pattern training are civil servant candidates from K1 and K2 honorarium employees who have worked as honorary employees for more than 10 (ten) years, where their age ranges from 30 s / d to 55 years. At such a young age, they certainly have different emotional intelligence. This research has a purpose to know the pattern of emotional intelligence of LPJ Special Pattern training participants at education office Pekanbaru City. This research is a quantitative descriptive research. Subjects in this study amounted to 30 employees. Data collection methods used in this study is the scale of emotional intelligence. Data analysis technique used is descriptive with quantitative approach. The result of the research shows that 13.3% of the participants of LPJ Special Education training in Pekanbaru education office have high level of emotional intelligence, 76,6% have moderate level of emotional intelligence, and only 10% have low emotional intelligence level.